2008
DOI: 10.1002/jcb.21819
|View full text |Cite
|
Sign up to set email alerts
|

Adeno‐associated virus‐mediated gene transfer

Abstract: Although the remarkable versatility and efficacy of recombinant adeno-associated virus 2 (AAV2) vectors in transducing a wide variety of cells and tissues in vitro, and in numerous pre-clinical animal models of human diseases in vivo, have been well established, the published literature is replete with controversies with regard to the efficacy of AAV2 vectors in hematopoietic stem cell (HSC) transduction. A number of factors have contributed to these controversies, the molecular bases of which have begun to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…In comparison with the prototypic AAV2, AAV vectors pseudotyped with other serotypes show superior transduction efficiency in various tissues: AAV1 in muscle, pancreatic islets, heart, vascular endothelium, brain, central nervous system (CNS) and liver; AAV3 in Cochlear inner hair cells; AAV4 in brain, lung, kidney, heart; AAV5 in brain and CNS, lung, eye, arthritic joints, and liver; AAV6 in heart, liver, skeletal muscle and airway epithelium; AAV7 in muscle, liver; AAV8 in muscle, pancreas, heart, and liver (Jiang et al 2006); AAV9 in heart, liver, CNS (Fechner et al 2008;Zincarelli et al 2008;Miyagi et al 2008;Klein et al 2008); AAV10 in CNS, hematopoietic stem cell (HSC), immune cells, skeletal muscle (Klein et al 2008;Maina et al 2008;Mori et al 2004Mori et al , 2008; AAV11 in immune cells, skeletal muscle (Mori et al 2004(Mori et al , 2008; AAV12 in HSC, muscle and salivary glands (Schmidt et al 2008;Srivastava 2008).…”
Section: Avv Serotypes As Gene Transfer Vectorsmentioning
confidence: 99%
“…In comparison with the prototypic AAV2, AAV vectors pseudotyped with other serotypes show superior transduction efficiency in various tissues: AAV1 in muscle, pancreatic islets, heart, vascular endothelium, brain, central nervous system (CNS) and liver; AAV3 in Cochlear inner hair cells; AAV4 in brain, lung, kidney, heart; AAV5 in brain and CNS, lung, eye, arthritic joints, and liver; AAV6 in heart, liver, skeletal muscle and airway epithelium; AAV7 in muscle, liver; AAV8 in muscle, pancreas, heart, and liver (Jiang et al 2006); AAV9 in heart, liver, CNS (Fechner et al 2008;Zincarelli et al 2008;Miyagi et al 2008;Klein et al 2008); AAV10 in CNS, hematopoietic stem cell (HSC), immune cells, skeletal muscle (Klein et al 2008;Maina et al 2008;Mori et al 2004Mori et al , 2008; AAV11 in immune cells, skeletal muscle (Mori et al 2004(Mori et al , 2008; AAV12 in HSC, muscle and salivary glands (Schmidt et al 2008;Srivastava 2008).…”
Section: Avv Serotypes As Gene Transfer Vectorsmentioning
confidence: 99%
“…83,90 The fact that they remain episomal eliminates the risk of insertional mutagenesis, although under rare circumstances it has been shown that the AAV genome can integrate. 91 A key advantage of rAAVs is that even though their genome remains episomal, they can still drive long-term expression. In several clinical trials, sustained transgene expression has been observed for 6 months to 3.7 years in patients 9295 and up to 8 years in primates and canine models.…”
Section: Viral Vectorsmentioning
confidence: 99%
“…99,141 Recent studies, however, suggest the occurrence at low frequency of such integration events in tissues such as cardiac and skeletal muscle, 142 although the induction tumourigenesis has been disputed. 91,143145 …”
Section: Viral Vectorsmentioning
confidence: 99%
“…These characteristics make AAV an appealing choice for gene transfer applications. Recombinant AAVs are being investigated as vectors for clinical gene transfer to a wide variety of cells and tissues (Hasbrouck and High, 2008; Kota et al, 2009; Maguire et al, 2009; Maguire et al, 2010; Muzyczka, 1992; Srivastava, 2008; Wagner et al, 1999). Transduction with AAV vectors has been shown to result in long-term transgene expression in vivo in several cell types including skeletal muscle, photoreceptors, liver, and neuronal cells (Daya and Berns, 2008; Hasbrouck and High, 2008; Liu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%